Arterial projectile embolism firearm: Communication of a case and review of the literature - Prego, Alfredo; Palacio, José L; Sosa, María C; Bergalli, Luis (Cirugía del Uruguay, 1994)
A case is presented of a patient with a bu/Jet injury in the left hemithorax whose projectile embolized and impacts in the popliteal artery determining accute arterial occlusion of the /eft /ower /imb. Epidemiological, pathogenical, diagnostica/ and therapeutical considerations are made as regards arterial and venous embolia due to fire-arm projectiles and bibliography on this rare complication of bu/Jet injuries is revised.